Primary neuroendocrine carcinoma of the breast: A rare entity (Indian Journal of Case Reports, 2020)
Neuroendocrine carcinomas of the breast are a rare and distinct entity that is not routinely encountered in clinical practice. The diagnosis of primary neuroendocrine breast carcinoma is mainly a diagnosis of exclusion as the metastatic disease is more common a possibility. The algorithmic approach in the evaluation of such tumors includes the clinical and radiological examination of the breast lumps followed by correlation with Histopathological study and Immunohistochemistry tests. We report a case of primary neuroendocrine carcinoma of the breast in a 64-year-old female who presented with breast lump for one month duration.